1992
DOI: 10.1016/0266-7681(92)90099-n
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Tuberculosis of a Skeletal Muscle

Abstract: A case is described of tuberculosis in the muscle belly of abductor pollicis longus in a 25-year-old Asian woman. The complaint was of swelling and, as there was no evidence of tuberculosis elsewhere, the diagnosis was not made until the lump was explored surgically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…These lesions may first be aspirated and cultured and treated with anti-tubercular drugs. The surgical option may be reserved for the following scenarios: (a) painful masses, rapidly enlarging, acting like space-occupying lesions and causing jeopardization of other functional structures in the vicinity (compartment-syndrome like situation) [11]; (b) recurrence after aspiration or debridement [5]; (c) immunocompromised state, where the bacterial load is high; (d) associated with bony destruction or sequestrum formation [12]; (e) doubtful diagnosis [3]; (f) non-responsiveness to antitubercular drugs despite culture being positive for M. tuberculosis; and (g) failed aspiration of the abscess and thereby lack of "effective" drainage.…”
Section: Discussionmentioning
confidence: 99%
“…These lesions may first be aspirated and cultured and treated with anti-tubercular drugs. The surgical option may be reserved for the following scenarios: (a) painful masses, rapidly enlarging, acting like space-occupying lesions and causing jeopardization of other functional structures in the vicinity (compartment-syndrome like situation) [11]; (b) recurrence after aspiration or debridement [5]; (c) immunocompromised state, where the bacterial load is high; (d) associated with bony destruction or sequestrum formation [12]; (e) doubtful diagnosis [3]; (f) non-responsiveness to antitubercular drugs despite culture being positive for M. tuberculosis; and (g) failed aspiration of the abscess and thereby lack of "effective" drainage.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed data from 58 literature cases identified from the systematic review and 11 survey cases identified from the multicenter study. Through a systematic literature search that was guided by the PRISMA guideline, we identified 52 articles (58 cases; Figure 1 ); six articles were case-series, and the rest were all case reports [ 7 , 12 - 62 ]. The quality assessment tool presented good correlation.…”
Section: Resultsmentioning
confidence: 99%
“…That is why we had advised for all patients FNAC and aspiration, and in some cases histopathological evaluation was done in which AFB staining failed to demonstrate acid fast bacilli. 15 On hematological evaluation laboratory parameters in patients with tuberculous pyomyositis may include low haemoglobin, leukocytosis, an elevated erythrocyte sedimentation rate (ESR), and elevated creatine phosphokinase (CPK) levels, though none of these is specific to this particular diagnosis and none are seen in each case. 16 Imaging modalities such as ultrasonography (USG), computed tomography scan (CT scan), and MRI is important in diagnosing pyomyositis.…”
Section: Discussionmentioning
confidence: 99%